The rescue a true story of courage and survival in World War II - Smith, Steven Trent 1947- (Wiley, 2001)
Chronicles the U.S. Navy's rescue of forty Americans stranded on a wartorn Philippine island--a mission resulting in the capture of documents that thwarted Japanese efforts to anhilate the Pacific Fleet and ensured American victory in the Battle of the Philippine Sea.
Keywords: Crevalle (Submarine); United States. -- Navy -- Search and rescue operations -- Philippines -- Negros Island; United States. -- Navy. -- Search and rescue operations -- Philippines -- Negros Island; Geschichte; Weltkrieg (1939-1945); World War, 1939-1945 -- Naval operations -- Submarine; World War, 1939-1945 -- Naval operations, American; World War, 1939-1945 -- Underground movements -- Philippines -- Negros; Soldat; Rettung; Zweiter Weltkrieg; Negros Island (Philippines) -- History; Philippines -- History -- Japanese occupation, 1942-1945; Philippinen; USA